PENAMPILAN REPRODUKSI TERNAK SAPI POTONG YANG DI INSEMINASI BUATAN DI KECAMATAN TOMBATU UTARA DAN KECAMATAN RATAHAN - Sawel, Ariny Irma; Lomboan, Agustinus; Paath, Jantje; Manopo, Jouke (ZOOTEC, 2019)
REPRODUCTIVE PERFORMANCE BEEF CATTLE OF ARTIFICIAL INSEMINATION IN THE DISTRICT OF NORTH TOMBATU AND SUB DISTRICT OF RATAHAN.   The porpose of this study to know appearance of reproduction beef cattle artificial insemination in the northern Tombatu District and the Sub District of Ratahan in the Southeast Minahasa Regency.  Research the everage valve standard deviation and coefficient of diversity.  Based on research results that service preconception 1.25-1.30, conception rate 70-75%, calving interval 366.4-377.55 and length of pregnancy 279.25-281.1 day. It can be colcluded that the reproductive performance of artificial insemination beef cattle in North Tombatu and Ratahan Districts already quite good. Keywords: Reproduction, beef cattle, artificial insemination